Housing Finance in Chile: Instruments, Actors, and Policies - Alejandro Micco; Eric Parrado; Bernardita Piedrabuena; Alessandro Rebucci (Inter-American Development Bank (IDB), 2012)
The Chilean system of housing finance is a mixture of public and private elements that has arguably been very successful. This paper provides an up- to-date review of the main instruments, actors, and government policies of the Chilean system of housing finance. It concludes that, while the system is indeed functioning well, the increasingly important role of BancoEstado warrants further analysis of the role of public banks in a modern, fully developed housing finance system.
Keywords: E52; F33; 330